Long-term effects of strength training on aerobic capacity and endurance performance - Sandbakk, O. (Concurrent aerobic and strength training. Scientific basics and practical applications, 2019)
Current scientific evidence suggests that heavy strength training can successfully be included in elite endurance athletes` training program, in order to build up and maintain strength and thereby positively influence aerobic capacity and endurance performance. In this chapter, scientific knowledge currently published on the long-term effects of strength training on aerobic capacity and endurance performance will be presented. Furthermore, the potential neural and cellular mechanisms related to these effects will be discussed. Overall, the presented chapter aims to summarize the literature and provide a framework for generating new hypotheses in this exciting area. Abstract from author